2008
DOI: 10.1093/aje/kwm370
|View full text |Cite
|
Sign up to set email alerts
|

Increased All-Cause, Liver, and Cardiac Mortality among Hepatitis C Virus-seropositive Blood Donors

Abstract: Hospital-based studies suggest that hepatitis C virus (HCV) infection causes frequent cirrhosis, hepatocellular carcinoma, and mortality, but epidemiologic studies have shown less morbidity and mortality. The authors performed a retrospective cohort study of 10,259 recombinant immunoblot assay-confirmed, HCV antibody-positive (HCV+), allogeneic blood donors from 1991 to 2002 and 10,259 HCV antibody-negative (HCV-) donors matched for year of donation, age, gender, and Zone Improvement Plan Code (ZIP Code). Vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 46 publications
5
99
1
1
Order By: Relevance
“…4 In another study of 10 259 anti-HCV seropositive and other 10 259 matched anti-HCV seronegative blood donors in the United States, the HR of death from stroke was 2.20 (0.84 to 5.79) for HCV infection. 23 The blood donor study essentially supported our findings with similar HR, but it was limited by the low statistical power to detect a significant association because of the small number (nϭ19) of cerebrovascular deaths in younger and generally healthier blood donors. Both studies may potentially be confounded by the inadequate adjustment of risk factors, including lifestyle habits, serum lipid profiles, and history of diseases.…”
Section: Discussionsupporting
confidence: 80%
“…4 In another study of 10 259 anti-HCV seropositive and other 10 259 matched anti-HCV seronegative blood donors in the United States, the HR of death from stroke was 2.20 (0.84 to 5.79) for HCV infection. 23 The blood donor study essentially supported our findings with similar HR, but it was limited by the low statistical power to detect a significant association because of the small number (nϭ19) of cerebrovascular deaths in younger and generally healthier blood donors. Both studies may potentially be confounded by the inadequate adjustment of risk factors, including lifestyle habits, serum lipid profiles, and history of diseases.…”
Section: Discussionsupporting
confidence: 80%
“…The authors performed a retrospective cohort study on 10 259 anti-HCV positive and 10 259 age and gender matched anti-HCV negative US blood donors, followed from 1991 to 2002, and with a mean follow-up of 7.7 years 28. Interestingly, they observed that the HCV positive group had excessive mortality due not only to higher liver, drug, alcohol and trauma/suicide related events, as expected, but also to an increase in cardiovascular mortality (HR=2.21) 28. Similar data were recently found in a community based long term prospective study in a cohort of 23 820 Taiwanese adults, enrolled from 1991 to 1992, and with follow-up data up to 2008 29.…”
Section: Evidence From Cohort and Prospective Studiesmentioning
confidence: 99%
“…[4][5][6] The impact of HCV infection on survival in the general population is controversial. Some studies have shown a significant increase in mortality in HCV-infected persons, 7,8 whereas others have shown relatively low mortality rate and liver disease progression in otherwise healthy persons. 9,10 In subsets of patients who have undergone liver transplantation, who have human immunodeficiency virus coinfection, or those on hemodialysis, HCV is associated with significantly shortened survival.…”
mentioning
confidence: 99%